Efeitos da época sobre os processos ecológicos em viveiros escavados para criação extensiva de tilápias no Sudeste do Brasil - Favaro, E. G.P. [UNESP]; Sipaúba-Tavares, L. H. [UNESP]; Milstein, A. (FapUNIFESP (SciELO), 2015)
In Southeastern Brazil tilapia culture is conducted in extensive and semi-intensive flow-through earthen ponds, being water availability and flow management different in the rainy and dry seasons. In this region lettuce wastes are a potential cheap input for tilapia culture. This study examined the ecological processes developing during the rainy and dry seasons in three extensive flow-through earthen tilapia ponds fertilized with lettuce wastes. Water quality, plankton and sediment parameters were sampled monthly during a year. Factor analysis was used to identify the ecological processes occurring within the ponds and to construct a conceptual graphic model of the pond ecosystem functioning during the rainy and dry seasons. Processes related to nitrogen cycling presented differences between both seasons while processes related to phosphorus cycling did not. Ecological differences among ponds were due to effects of wind protection by surrounding vegetation, organic loading entering, tilapia density and its grazing pressure on zooplankton. Differences in tilapia growth among ponds were related to stocking density and ecological process affecting tilapia food availability and intraspecific competition. Lettuce wastes addition into the ponds did not produce negative effects, thus this practice may be considered a disposal option and a low-cost input source for tilapia, at least at the amounts applied in this study.
Effects of season on ecological processes in extensive earthen tilapia ponds in Southeastern Brazil
Keywords: Earthen pond ecology; Flow-through; Seasonal variations; Tilapia extensive culture; Water quality